The Application of Multitasking For Maximizing Staff Effectiveness During The Covid-19 Era at Most Blue Bali Resort - Gde Yudhie Adhitya Surya Pratama; Ni Nyoman Triyuni; I Wayan Basi Arjana; Made Ruki; Ni Wayan Wahyu Astuti (International Journal of Travel, Hospitality and Events, 2023)
Purpose: This research was conducted to examine the effect of multitasking on quality performance for maximizing staff effectiveness during the Covid-19 era at Most Blue Bali Resort. Research methods: The sample used in this study amounted to 30 respondents—the sampling method used simple sampling. The data analysis method used is a quantitative analysis using validity and reliability tests, classical assumption test, F test, coefficient of determination, t-test, and multiple regression analysis. Results and discussion: Using the multiple regression method, it can be concluded that the amount of multitasking variable has a positive and significant effect on customer satisfaction with a significance value (P value) of 0.0030<0.05. Age has a positive but insignificant effect on customer satisfaction with a significance value (P value) of 0.727>0.05. The method of task completion has a positive but insignificant impact on customer satisfaction with a significance value (P value) of 0.080>0.05. The position has a positive but insignificant effect on customer satisfaction with a significance value (P value) of 0.383>0.05. Simultaneously, the amount of multitasking, age, method of task completion, and position has a significant effect on customer satisfaction with an F count of 11.217 with a significance figure (P value) of 0.000<0.05. Implication: The resulting coefficient of determination is 0.58, which means that 58 percent of changes in the quality performance variable are explained by the amount of multitasking, age, method of task completion, and position together, while the remaining 52 percent is explained by other variables not included in this research. Keywords: multitask, quality performance, influence, application.